Analysis Of Job Burden Using Method of FTE (Full Time Equivalent) at Puskesmas Pantoloan - Yenita Ayudina; Sudirman Sudirman; Nurjanah Nurjanah (Universitas Muhammadiyah Palu, 2021)
Health development is an integral and important part of national development. The objective of implementing health development is to increase awareness, willingness, and ability to be alive healthy for everybody to create a degree of optimal public health. The advance of health development is not absent from health staffs in it, competent health staff s in their fields and an appropriate number of staffs at every facility of service decided given service quality. To meet the number of staff e appropriately with the demand of health service facilities. job burden analysis is carried out. There are some methods used to do job burden analysis. In this research, the researcher used the method of FTE (Full Time Equivalent) to carry out an analysis of job burden. This research used a descriptive with a qualitative approach, conducting observation, deep interview, and documentation. The informant of this research is ane staff whole plays role as the manager of ABKÂ data (analysis of job burden) at Puskesmas Pantoloan. Research findings show that the computation result of job burden analysis that used method of Full-Time Equivalent (FTE) job burden of health staffs at Puskesmas Pontoloan is overload category because FTE index which is obtained is 2,7. The conclusion of research findings shows that computation result of job burden analysis that used Full-Time Equivalent (FTE) show that job burden of nine kinds of health staffs at Puskesmas Pantoloan include overload category with FTE index 2,7 indicated that the number of health staffs is less than job burden accepted by health staff.